(untitled) (European Journal of Formal Sciences and Engineering, 2019)
Why habitat Mars when you can make earth livable. Demographic change led to the shrinking of the city and also aging native population were big problems in leinefelde. Sustainable urban structures, housing affordability and availability was a big criteria. The political and economic change in the eastern Germany after reunification in 1989, anticipated and intensified the problems. By 1993 municipality realized that it should develop strategies and policies to stop the breakdown of economic and political breakdown of the city. As a result of the actions taken, leinefelde has become successful transformation of shrinking cities in the world. This research paper finds the problems led to shrinking of the city and then focuses on the different parameters and strategies like project context, social aspects, environmental aspects, economic aspects, organizational aspects, sustainable aspects that were carried out in order to have a successful transformation of leinefelde. And finally list down the key indicator for project being successful as a conclusion.